AN ITERATIVE ALGORITHM OF DISPATCHING CONTROL - V. N. Nikonov; M. V. Silivonets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An iterative algorithm of dispatching control, exceeding standart algorithms in terms of throughput, passengers service quality and energy efficiency is created.